A membrane electrode for producing hydrogen by alkaline water electrolysis and its preparation method and application

By filling the membrane electrode with opposite conductivity types of semiconductor particles to form PN junctions, the problem of low electrolysis efficiency of membrane electrodes during alkaline electrolysis is solved, and the utilization rate of catalysts and stack performance is improved, which is close to that of precious metal catalysts. performance.

CN117926313BActive Publication Date: 2025-01-03GUONENG SCIENTIFIC & TECHNOLOGICAL ACHIEVEMENTS TRANSFORMATION (BEIJING) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310804554.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-03
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The electrolytic efficiency of the membrane electrode during the existing alkaline electrolysis process is low, resulting in poor conductivity and insufficient stability of the catalyst, and it is impossible to effectively overcome the high cost and storage limits of precious metal electrodes.

Method used

The anode catalyst layer and the cathode catalyst layer of the membrane electrode are filled with opposite conductivity types, forming a PN junction, and contacting the semiconductor layer to achieve electrocatalytic conduction, improving the utilization rate of the catalyst and the stack current density.

Benefits of technology

By forming a PN junction, the catalytic efficiency and stack current density of the membrane electrode are improved, the ohmic resistance and energy consumption are reduced, and the performance of the catalyst is close to that of the noble metal catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117926313B_ABST
    Figure CN117926313B_ABST
Patent Text Reader

Abstract

The present invention provides a membrane electrode and a preparation method and application thereof, wherein the membrane electrode comprises: a diaphragm and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the diaphragm, wherein the anode catalyst layer and / or the cathode catalyst layer are covered with a semiconductor layer on a side different from the diaphragm; the gaps between the catalysts in the anode catalyst layer and / or the cathode catalyst layer are filled with semiconductor particles of the opposite conductivity type to the semiconductor layer, wherein the semiconductor particles are in direct contact with the semiconductor layer to form a PN junction and can be electrically catalytically connected with the catalyst. The catalyst coated with a binder in the membrane electrode of the present invention can also conduct electricity to generate a catalytic reaction, and also increases the electrochemical active area of ​​the membrane electrode, improves the catalytic efficiency of the membrane electrode and the current density of the stack, and reduces the ohmic resistance and the energy consumption of the stack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production by alkaline water electrolysis, and in particular, relates to a membrane electrode and a preparation method and application thereof. Background Art

[0002] In order to reduce dependence on fossil fuels, renewable energy has always been a global research hotspot. New energy is energy that is developed and researched outside the scope of traditional energy, such as hydrogen energy, nuclear energy, wind energy, solar energy and bioenergy. Hydrogen energy has the advantages of high combustion enthalpy and zero emissions, meeting the needs of green new energy. Hydrogen production by water electrolysis is considered to be the most economical and efficient way to produce hydrogen. Compared with traditional acidic water electrolysis, alkaline water electrolysis usually uses cheap catalysts and can be industrialized at the same time with the anode half-reaction (oxygen evolution or chlorine evolution). Due to the problems of low current density and poor stability in the process of alkaline water electrolysis, precious metals with high exchange current density are generally used as electrodes for alkaline water electrolysis. However, considering the price and storage capacity of precious metals, people have conducted a series of studies to improve the activity of existing alkaline water electrolysis hydrogen production catalysts and accelerate the reaction rate.

[0003] Chinese patent ZL202010603361.0 provides an ink-assisted synthesized molybdenum carbide / carbon nano electrocatalytic hydrogen production catalyst, in which molybdenum carbide nanoparticles and carbon nanoparticles are cross-composed. The molybdenum carbide nanoparticles are located at the active center of the catalyst, and the carbon nanoparticles are derived from the ink. The carbon nanoparticles have a graphite-like structure, carry a negative charge, and have a three-dimensional hierarchical porous structure, which can effectively promote the transfer of electrolytes and the diffusion of the generated hydrogen bubbles, reduce the overpotential in the process of hydrogen production by electrolysis of water, and obtain excellent electrocatalytic hydrogen production activity and stability.

[0004] Chinese patent application 202110959098.3 provides a method for preparing a nickel-cobalt-phosphorus high-efficiency catalyst, which is prepared by preparing chemical plating solutions of different proportions, using metal foam as a substrate, and depositing a nickel-cobalt-phosphorus high-efficiency composite catalyst at different reaction temperatures and different reaction times. In the composite catalyst prepared by the method, the nickel-cobalt-phosphorus active substance is directly deposited on the metal foam to avoid the use of a binder, increase the electrochemical performance of the catalyst in an alkaline electrolyte, improve its conductivity and stability, and increase the electron transfer rate.

[0005] However, the actual alkaline water electrolysis hydrogen production still has the problem of low electrolysis efficiency of membrane electrodes. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art, provide a membrane electrode and a preparation method and application thereof, and improve the electrolysis efficiency of the membrane electrode in the process of alkaline water electrolysis to produce hydrogen.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a membrane electrode, which includes: a diaphragm and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the diaphragm, the anode catalyst layer and / or the cathode catalyst layer are covered with a semiconductor layer on a side different from the diaphragm; the gaps between the catalysts in the anode catalyst layer and / or the cathode catalyst layer are filled with semiconductor particles of the opposite conductivity type to the semiconductor layer, the semiconductor particles are in direct contact with the semiconductor layer to form a PN junction, and can be electrically catalytically conductive with the catalyst.

[0008] Optionally, the semiconductor particles in the anode catalyst layer are P-type semiconductor powder, and the semiconductor layer in contact with the anode catalyst layer is a first semiconductor layer; the semiconductor particles in the cathode catalyst layer are N-type semiconductor powder, and the semiconductor layer in contact with the cathode catalyst layer is a second semiconductor layer; the first semiconductor layer includes a film layer composed of an N-type semiconductor or a supporting substrate loaded with an N-type semiconductor; the second semiconductor layer includes a film layer composed of a P-type semiconductor or a supporting substrate loaded with a P-type semiconductor.

[0009] Optionally, the N-type semiconductor is selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4, Fe2O3 and BaTiO3;

[0010] The P-type semiconductor is selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3, Bi2Te3 and MoO2.

[0011] Optionally, the film layer composed of the N-type semiconductor or the film layer composed of the N-type semiconductor has a thickness of 1-30 μm;

[0012] The support substrate is selected from nickel mesh, titanium mesh, molybdenum mesh, stainless steel mesh, porous nickel, porous titanium, foamed nickel and foamed titanium; the mesh size of the nickel mesh, titanium mesh, molybdenum mesh and stainless steel mesh is 40-100 mesh; the porosity of the porous nickel, porous titanium, foamed nickel and foamed titanium is 40-95%.

[0013] Optionally, the particle size of the semiconductor particles is 10-50 nm; the particle size of the catalyst is 0.05-10 μm.

[0014] Optionally, the thickness of the anode catalyst layer is 10-200 μm; the thickness of the cathode catalyst layer is 1-200 μm; and the mass ratio of the catalyst to the semiconductor particles is 1:(0.05-0.5).

[0015] Preferably, the thickness of the anode catalyst layer is 20-100 μm;

[0016] The thickness of the cathode catalyst layer is 5-100 μm;

[0017] The mass ratio of the catalyst to the semiconductor particles is 1:(0.05-0.2).

[0018] Optionally, the catalyst in the anode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys or oxides or metal salts; the catalyst in the cathode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts; the diaphragm is selected from one or more of polyphenylene sulfide (PPS) diaphragm, polyetheretherketone fiber diaphragm and polysulfone fiber diaphragm.

[0019] Preferably, the catalyst in the anode catalyst layer is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy;

[0020] The catalyst in the cathode catalyst layer is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2.

[0021] A second aspect of the present invention provides a method for preparing a membrane electrode, the method comprising: preparing an anode slurry and / or a cathode slurry doped with semiconductor particles respectively;

[0022] Applying the anode slurry and cathode slurry to both sides of the diaphragm respectively;

[0023] Coating a semiconductor compound film layer having a conductivity type opposite to that of the semiconductor particles on the catalyst coating layer containing the semiconductor particles to form a membrane electrode; and / or

[0024] A catalyst layer is formed from a slurry containing semiconductor particles and a support substrate is covered on the catalyst layer. The support substrate carries a semiconductor compound of a conductivity type opposite to that of the semiconductor particles.

[0025] Optionally, the method of forming a membrane electrode and forming a catalyst layer from a slurry containing semiconductor particles comprises vacuum drying and hot pressing, the drying temperature is 50-150° C., the drying time is 1-3 hours; the hot pressing temperature is 80-200° C., and the hot pressing pressure is 20-100 bar.

[0026] Optionally, the method for preparing the anode slurry and / or cathode slurry doped with semiconductor particles comprises:

[0027] Taking an anode catalyst and a P-type semiconductor powder and mixing them evenly to obtain an anode mixed powder;

[0028] Taking cathode catalyst and N-type semiconductor powder and mixing them evenly to obtain cathode mixed powder;

[0029] The anode mixed powder or cathode mixed powder is uniformly stirred with a thickener, a dispersant, a binder and a solvent to obtain an anode slurry or a cathode slurry;

[0030] The amount of the semiconductor particles is 5-50wt% based on the weight of the catalyst in the anode slurry or the cathode slurry;

[0031] The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):1.

[0032] Optionally, the binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyethersulfone and fluororesin;

[0033] The dispersant is a phosphate dispersant or an acrylic dispersant, preferably one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt;

[0034] The thickener is selected from one or more of cellulose ether thickeners, polyurethane thickeners and modified polyurea thickeners;

[0035] The solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol, preferably one or more of water, ethanol and isopropanol.

[0036] A third aspect of the present invention provides an electrolytic cell, which is provided with the membrane electrode according to the first aspect of the present invention.

[0037] Through the above technical scheme, the anode catalyst layer and / or cathode catalyst layer of the membrane electrode of the present invention is filled with semiconductor particles, the semiconductor layer and the semiconductor particles have opposite conductivity types and form a PN junction, the semiconductor particles can conduct the catalyst of the anode or cathode through electrocatalytic electrons, and the catalyst coated by the binder can also conduct electricity to produce a catalytic reaction, thereby improving the catalytic efficiency of the membrane electrode.

[0038] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0040] Figure 1 It is a structural exploded diagram of a membrane electrode according to an embodiment of the present invention.

[0041] Figure 2 It is a schematic diagram of the structure of a membrane electrode according to an embodiment of the present invention. DETAILED DESCRIPTION

[0042] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0043] The alkaline electrolysis of water to produce hydrogen has the following half-reactions:

[0044] Cathode 4H2O+4e→4OH - +2H2φ θ H2O / H2=0.829V

[0045] Anode 4OH - -4e→2H2O+O2φ θ O2 / OH - =-0.401V

[0046] During water electrolysis, the thermodynamic voltage of water decomposition is 1.23V, but in the actual water electrolysis process, a voltage higher than 1.23V is usually applied to overcome the activation barrier inherent in the anode and cathode. Precious metals have high activity and low overpotential, and are very good hydrogen production electrode materials, but they are expensive. Therefore, it is of great significance to improve the electrocatalytic performance of existing electrodes using non-precious metal catalysts. The inventors found that the conductivity of catalysts in existing alkaline water electrolysis hydrogen production technology is not good, but the high temperature and strong alkali characteristics of alkaline water electrolysis electrolyzers make some high-efficiency conductive agents (such as conductive carbon) unusable, and the added binder easily causes the active sites of the catalyst to be covered, and the utilization rate of the catalyst is not high, resulting in a decrease in the efficiency of membrane electrode water electrolysis during alkaline water electrolysis hydrogen production. Therefore, the present invention is proposed, which can gradually make the catalytic performance of existing catalysts close to that of precious metal catalysts.

[0047] The first aspect of the present invention provides a membrane electrode, which includes: a diaphragm and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the diaphragm, wherein the anode catalyst layer and / or the cathode catalyst layer is covered with a semiconductor layer on a surface different from the side of the diaphragm; the gaps between the catalysts in the anode catalyst layer and / or the cathode catalyst layer are filled with semiconductor particles of the opposite conductivity type to the semiconductor layer, the semiconductor particles are in direct contact with the semiconductor layer to form a PN junction, and can be electrically catalytically conductive with the catalyst.

[0048] In the present invention, semiconductor particles may be doped only in the anode catalyst layer or the cathode catalyst layer, or may be doped in both the anode catalyst layer and the cathode catalyst layer at the same time, and then a semiconductor layer is arranged on the catalyst layer doped with semiconductor particles so that the semiconductor particles are in contact with the semiconductor layer to form a PN junction.

[0049] In the present invention, the PN junction is a transition zone formed by the interface between an N-type semiconductor and a P-type semiconductor, that is, the PN junction refers to the contact surface between a P-type semiconductor and an N-type semiconductor. N-type semiconductors are prone to generate free electrons, and P-type semiconductors are prone to generate holes, i.e., positive electricity. Direct contact between the two can generate a built-in electric field. Under a forward voltage, electrons move from an N-type semiconductor to a P-type semiconductor, and holes move from a P-type semiconductor to an N-type semiconductor, thereby generating current to achieve unidirectional conduction.

[0050] In the membrane electrode of the present invention, the semiconductor layer and the semiconductor particles have opposite conductivity types and form a PN junction, which can conduct the catalyst in the anode or cathode through electrocatalytic electrons. The catalyst coated by the binder can also conduct electricity to produce a catalytic reaction, thereby improving the catalytic efficiency of the membrane electrode and the current density of the battery stack, reducing the ohmic resistance and the energy consumption of the battery stack, and making the catalytic performance of the catalyst close to that of precious metal catalysts such as Pt.

[0051] Wherein, the semiconductor particles in the anode catalyst layer are P-type semiconductor powders, and the semiconductor layer in contact with the anode catalyst layer is a first semiconductor layer;

[0052] The semiconductor particles in the cathode catalyst layer are N-type semiconductor powders, and the semiconductor layer in contact with the cathode catalyst layer is a second semiconductor layer.

[0053] Wherein, the first semiconductor layer includes a film layer composed of an N-type semiconductor or a supporting substrate loaded with an N-type semiconductor;

[0054] The second semiconductor layer includes a film layer composed of a P-type semiconductor or a supporting substrate loaded with a P-type semiconductor.

[0055] The semiconductor film or the semiconductor-loaded support substrate at least covers the surface of the catalyst layer that is different from the diaphragm. The catalyst layer is in contact with the semiconductor layer, which is conducive to forming a PN junction between the semiconductor particles in the catalyst layer and the semiconductor in the semiconductor layer. The method of loading the semiconductor on the support substrate is mainly sintering. The introduction of the support substrate can also improve the mechanical strength of the membrane electrode and increase the pressure resistance range of the electrolytic cell when electrolyzing water.

[0056] The semiconductor layers used as the anode and cathode can be the same or different. For example, the semiconductor layers of the anode and cathode can be both semiconductor films or supporting substrates loaded with semiconductors. Alternatively, the semiconductor layer of one of the anode or cathode can be a semiconductor film, and the semiconductor layer of the other can be a supporting substrate loaded with semiconductors.

[0057] refer to Figure 1 The membrane electrode of the present invention comprises a diaphragm 10 and catalyst layers respectively arranged on both sides of the diaphragm 10, and the catalyst layer is different from the diaphragm and has a semiconductor layer on one side. The catalyst layer comprises an anode catalyst layer and a cathode catalyst layer. Figure 1 As an exploded view of a membrane electrode according to an embodiment of the present invention, the anode catalyst layer 20 is located on one side of the diaphragm, and the cathode catalyst layer 30 is located on the other side of the diaphragm. The semiconductor particles in the anode catalyst layer 20 are P-type semiconductor powders, and the anode side semiconductor layer is a support substrate 40 loaded with N-type semiconductors; the semiconductor particles in the cathode catalyst layer 30 are N-type semiconductor powders, and the cathode layer semiconductor layer is a support substrate 50 loaded with P-type semiconductors.

[0058] The semiconductor layer may also be a film layer composed of a semiconductor, and the thickness of the semiconductor layer may be 1-30 μm. Figure 2 This is a schematic diagram of another embodiment of the present invention, wherein the anode catalyst layer 20 includes an anode catalyst 21 and P-type semiconductor particles 22 filling gaps formed between the anode catalysts 21, and the semiconductor layer 40 is a film layer composed of an N-type semiconductor, and the N-type semiconductor film covers the surface of the anode catalyst layer 20. The P-type semiconductor particles 22 form a PN junction with the N-type semiconductor film, and the anode catalyst 21 can be turned on by electrocatalysis, so that the covered sites on the anode catalyst 21 can also undergo catalytic reactions.

[0059] Wherein, the N-type semiconductor is selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4, Fe2O3 and BaTiO3; the P-type semiconductor is selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3, Bi2Te3 and MoO2. By selecting the powder of the N-type semiconductor and the powder of the P-type semiconductor of the above types and making them contact, a PN junction can be fully formed, and the electrocatalytic conduction efficiency is optimal.

[0060] Wherein, the film layer formed by the N-type semiconductor or the film layer formed by the N-type semiconductor has a thickness of 1-30 μm.

[0061] Wherein, the support substrate is selected from nickel mesh, titanium mesh, molybdenum mesh, stainless steel mesh, porous nickel, porous titanium, foamed nickel and foamed titanium. Preferably, the mesh number of the nickel mesh, titanium mesh, molybdenum mesh and stainless steel mesh is 40-100 mesh, and the porosity of the porous nickel, porous titanium, foamed nickel and foamed titanium is 40-95%. Preferably, when sintering the semiconductor on the support substrate, the metal support substrate needs to be surface treated to remove oil stains and metal oxides on its surface.

[0062] Wherein, the particle size of the semiconductor particles is 10-50 nm; the particle size of the catalyst is 0.05-10 μm.

[0063] The mass ratio of the catalyst to the semiconductor particles is 1:(0.05-0.5).

[0064] By selecting semiconductor particles and catalysts of appropriate particle sizes, the semiconductor particles can be fully filled in the gaps formed between the catalysts. At the same time, controlling the mass ratio of semiconductor particles to catalysts can improve the utilization rate of the catalyst and obtain better catalytic efficiency. Preferably, the mass ratio of the catalyst to the semiconductor particles is 1: (0.05-0.2).

[0065] The thickness of the anode catalyst layer is 10-200 μm, and the thickness of the cathode catalyst layer is 1-200 μm. Controlling the thickness of the anode catalyst layer and the cathode catalyst layer can control the total loading of the anode catalyst or the cathode catalyst to obtain higher catalytic activity without making the resistance of the catalyst layer too large.

[0066] Preferably, the thickness of the anode catalyst layer is 20-100 μm; the thickness of the cathode catalyst layer is 5-100 μm.

[0067] Wherein, the catalyst in the anode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys, oxides or metal salts;

[0068] The catalyst in the cathode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts;

[0069] The diaphragm is selected from one or more of a polyphenylene sulfide (PPS) diaphragm, a polyetheretherketone fiber diaphragm and a polysulfone fiber diaphragm.

[0070] Preferably, the catalyst in the anode catalyst layer is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy;

[0071] The catalyst in the cathode catalyst layer is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2.

[0072] A second aspect of the present invention provides a method for preparing a membrane electrode, the method comprising:

[0073] Separately preparing anode slurry and / or cathode slurry doped with semiconductor particles; coating the anode slurry and cathode slurry on both sides of the diaphragm respectively;

[0074] Coating a semiconductor compound film layer having a conductivity type opposite to that of the semiconductor particles on the catalyst coating layer containing the semiconductor particles to form a membrane electrode; and / or

[0075] A catalyst layer is formed from a slurry containing semiconductor particles and a support substrate is covered on the catalyst layer. The support substrate carries a semiconductor compound of a conductivity type opposite to that of the semiconductor particles.

[0076] Methods for coating the anode slurry or cathode slurry on the diaphragm include, but are not limited to, spraying, scraping, magnetron sputtering, etc. For example, screen printing, dipping, etc. can also be used to evenly distribute the catalyst slurry on the surface of the diaphragm.

[0077] In the present invention, the support substrate is selected from nickel mesh, titanium mesh, molybdenum mesh, stainless steel mesh, porous nickel, porous titanium, foamed nickel and foamed titanium.

[0078] The method of forming a membrane electrode and forming a catalyst layer from a slurry containing semiconductor particles comprises vacuum drying and hot pressing, the drying temperature is 50-150°C, the drying time is 1-3h; the hot pressing temperature is 80-200°C, and the hot pressing pressure is 20-100bar.

[0079] Preferably, the drying temperature is 50-100° C., and the drying time is 1-2 hours; the hot pressing temperature is 100-190° C., and the hot pressing pressure is 30-70 bar.

[0080] Wherein, the preparation method of the anode slurry and / or cathode slurry doped with semiconductor particles comprises:

[0081] Taking an anode catalyst and a P-type semiconductor powder and mixing them evenly to obtain an anode mixed powder;

[0082] Taking cathode catalyst and N-type semiconductor powder and mixing them evenly to obtain cathode mixed powder;

[0083] The anode mixed powder or cathode mixed powder is uniformly stirred with a thickener, a dispersant, a binder and a solvent to obtain an anode slurry or a cathode slurry;

[0084] The amount of the semiconductor particles is 5-50wt% based on the weight of the catalyst in the anode slurry or the cathode slurry;

[0085] The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10): 1. By adding a suitable amount of semiconductor particles to the anode slurry or the cathode slurry, the semiconductor particles can be fully dispersed in the slurry without affecting the performance of the slurry in various aspects, while making the catalyst layer have better catalytic activity.

[0086] Among them, the binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyether sulfone and fluororesin; the dispersant is a phosphate dispersant or an acrylic dispersant, preferably one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt; the thickener is selected from one or more of cellulose ether thickener, polyurethane thickener and modified polyurea thickener; the solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol, preferably one or more of water, ethanol and isopropanol.

[0087] A third aspect of the present invention provides an electrolytic cell, which is provided with the membrane electrode according to the first aspect of the present invention.

[0088] The present invention is further described in detail by the following examples, but the present invention is not limited to the following examples. The raw materials used in the following examples can be obtained through commercial channels unless otherwise specified.

[0089] Example 1

[0090] Example 1 A membrane electrode E1 in which a P-type semiconductor powder is doped in an anode catalyst layer is prepared. The preparation method comprises the following steps:

[0091] (1) P-type semiconductor powder or nanosheets and anode catalyst are placed in a mortar and ground for 2 h until they are evenly mixed to obtain anode mixed powder; wherein the anode catalyst is NiCo2O4 and the P-type semiconductor is NiO; and the mass ratio of the anode catalyst to the P-type semiconductor is 1:0.1;

[0092] (2) Add part of the solvent to the anode mixed powder and thickener and disperse them by ball milling, then add the dispersant, binder and the remaining solvent and stir at a low speed for 10 hours; wherein the thickener is CMC (sodium carboxymethyl cellulose), the dispersant is sodium hexametaphosphate, the binder is perfluorosulfonic acid resin binder, and the solvent is water; the mass ratio of the anode catalyst to the thickener, dispersant, binder and solvent is 1:0.001:0.001:1:0.5, and obtain an anode slurry doped with semiconductor particles;

[0093] The cathode catalyst and thickener are added to a part of the solvent and ball-milled for dispersion, and then a dispersant, a binder and the remaining solvent are added and stirred at a low speed for 12 hours; wherein the thickener is carboxymethyl cellulose, the dispersant is potassium tripolyphosphate, the binder is perfluorosulfonic acid resin, and the solvent is water; the mass ratio of the cathode catalyst to the thickener, the dispersant, the binder and the solvent is 1:0.01:0.01:0.5:0.5, and a cathode slurry is obtained;

[0094] (3) The anode slurry doped with semiconductor particles is coated on one side of the diaphragm with a spray gun, and the cathode slurry is coated on the other side. The thickness of the slurry coated on the anode side of the diaphragm is 50 μm, and the thickness of the slurry coated on the cathode side is 50 μm. Then, a layer of N-type semiconductor film is coated on the anode side slurry with a spray gun. The thickness of the N-type semiconductor film is 10 μm. After coating, it is placed in a vacuum oven for drying, and then hot-pressed to prepare a conductive film electrode. The N-type semiconductor is Fe3O4, the drying temperature is 100°C, and the drying time is 2 h. The hot-pressing temperature is 150°C and the pressure is 60 bar.

[0095] Example 2

[0096] Example 2 A membrane electrode E2 in which the anode catalyst layer is doped with P-type semiconductor powder is prepared. The method for preparing the membrane electrode in this example is the same as that in Example 1, and the difference from Example 1 is that:

[0097] In step (1), the anode catalyst is LaNiO3, the P-type semiconductor is CoO, and the mass ratio of the anode catalyst to the P-type semiconductor is 1:0.05;

[0098] In step (3), the thickness of the slurry coated on the anode side of the diaphragm is 60 μm, and the thickness of the slurry coated on the cathode side is 60 μm. The N-type semiconductor forming the semiconductor film is V3O8.

[0099] Example 3

[0100] Example 3 A membrane electrode E3 in which a P-type semiconductor powder is doped in the anode catalyst layer is prepared. The method for preparing the membrane electrode in this example is the same as that in Example 1, and the difference from Example 1 is that:

[0101] In step (1), the anode catalyst is RanyNi, the P-type semiconductor is Bi2Te3, and the mass ratio of the anode catalyst to the P-type semiconductor is 1:0.08;

[0102] In step (2), the thickener is CMC, the dispersant is sodium hexametaphosphate, the binder is polytetrafluoroethylene resin binder, and the solvent is water; the mass ratio of the anode catalyst to the thickener, dispersant, binder, and solvent is 1:0.003:0.005:1.2:0.8.

[0103] Example 4

[0104] Example 4 A membrane electrode E4 in which the anode catalyst layer is doped with P-type semiconductor powder and the cathode catalyst layer is doped with N-type semiconductor powder is prepared. The preparation method includes the following steps:

[0105] (1) P-type semiconductor powder or nanosheets and anode catalyst are placed in a mortar and ground for 2 hours until they are evenly mixed to obtain anode mixed powder; wherein the anode catalyst is RanyNi, the P-type semiconductor is Bi2Te3, and the mass ratio of the anode catalyst to the P-type semiconductor is 1:0.1; N-type semiconductor powder or nanosheets and cathode catalyst are placed in a mortar and ground for 3 hours until they are evenly mixed to obtain cathode mixed powder; wherein the cathode catalyst is RanyNi, the N-type semiconductor is WO3, and the mass ratio of the cathode catalyst to the N-type semiconductor is 1:0.08;

[0106] (2) Add part of the solvent to the anode mixed powder and thickener and disperse them by ball milling, then add the dispersant, binder and the remaining solvent and stir at a low speed for 10 hours; wherein the thickener is a modified polyurethane thickener, the dispersant is an acrylic copolymer, the binder is a polyethersulfone resin solution, and the solvent is propanol; the mass ratio of the anode catalyst to the thickener, dispersant, binder and solvent is 1:0.04:0.01:1.5:1, and obtain an anode slurry doped with semiconductor particles;

[0107] The cathode mixed powder and thickener are added with a part of the solvent for ball milling dispersion, and then the dispersant, binder and the remaining solvent are added and stirred at a low speed for 12 hours; wherein the thickener is a modified polyurethane thickener, the dispersant is an acrylic copolymer, the binder is a polyethersulfone resin solution, and the solvent is propanol; the mass ratio of the cathode catalyst to the thickener, dispersant, binder and solvent is 1:0.01:0.05:1:1, and a cathode slurry doped with semiconductor particles is obtained;

[0108] (3) The anode slurry doped with semiconductor particles is coated on one side of the diaphragm by a spray gun, and the cathode slurry doped with semiconductor particles is coated on the other side. The thickness of the slurry coated on the anode side of the diaphragm is 100 μm, and the thickness of the slurry coated on the cathode side is 50 μm. Then, a layer of N-type semiconductor film is coated on the anode side slurry by a spray gun, and a layer of P-type semiconductor film is coated on the cathode side slurry. After coating, the slurry is placed in a vacuum oven for drying, and then hot-pressed to prepare a conductive film electrode. The N-type semiconductor is V2O5, and the P-type semiconductor is Bi2Te3. The drying temperature is 120°C, and the drying time is 2 h. The hot-pressing temperature is 150°C and the pressure is 60 bar.

[0109] Example 5

[0110] Example 5 A membrane electrode E5 in which the anode catalyst layer is doped with P-type semiconductor powder is prepared. The method for preparing the membrane electrode in this example is the same as that in Example 1, and the difference from Example 1 is that:

[0111] In step (3), the anode slurry doped with semiconductor particles is coated on one side of the diaphragm with a spray gun, and the cathode slurry is coated on the other side. The thickness of the slurry coated on the anode side of the diaphragm is 50 μm, and the thickness of the slurry coated on the cathode side is 50 μm. After coating, it is placed in a vacuum oven for drying, and then hot-pressed. A layer of nickel mesh sintered with N-type semiconductor is covered on the hot-pressed anode catalyst layer to prepare a conductive membrane electrode; wherein the N-type semiconductor is BaTiO3, the drying temperature is 100°C, and the drying time is 2 h; the hot-pressing temperature is 150°C and the pressure is 60 bar.

[0112] Example 6

[0113] Example 6 A membrane electrode E6 in which the anode catalyst layer is doped with P-type semiconductor powder is prepared. The method for preparing the membrane electrode in this example is the same as that in Example 1, and the difference from Example 1 is that:

[0114] In step (1), the anode catalyst is NiCo2O4, the P-type semiconductor is Sb2S3; the mass ratio of the anode catalyst to the P-type semiconductor is 1:0.1;

[0115] In step (3), the anode slurry doped with semiconductor particles is coated on one side of the diaphragm with a spray gun, and the cathode slurry is coated on the other side, the thickness of the slurry coated on the anode side of the diaphragm is 50 μm, and the thickness of the slurry coated on the cathode side is 50 μm; after coating, it is placed in a vacuum oven for drying, and then hot pressed, and a layer of stainless steel mesh sintered with N-type semiconductor is covered on the hot-pressed anode catalyst layer to prepare a conductive membrane electrode; wherein the N-type semiconductor is V3O8, the drying temperature is 120°C, and the drying time is 2h; the hot pressing temperature is 150°C and the pressure is 60 bar.

[0116] Example 7

[0117] Example 7 A membrane electrode E7 in which the anode catalyst layer is doped with P-type semiconductor powder and the cathode catalyst layer is doped with N-type semiconductor powder is prepared. The method for preparing the membrane electrode in this example is the same as that in Example 4, and the difference from Example 4 is that:

[0118] In step (3), an anode slurry doped with semiconductor particles is sprayed on one side of the diaphragm, and a cathode slurry doped with semiconductor particles is sprayed on the other side, the thickness of the slurry coated on the anode side of the diaphragm is 100 μm, and the thickness of the slurry coated on the cathode side is 50 μm; after coating, it is placed in a vacuum oven for drying, and then hot pressed, and a layer of nickel mesh sintered with N-type semiconductor is covered on the hot-pressed anode catalyst layer, and a layer of nickel mesh sintered with P-type semiconductor is covered on the cathode catalyst layer, so as to prepare a conductive membrane electrode; wherein the N-type semiconductor sintered on the nickel mesh is V2O5, and the P-type semiconductor is NiO; the drying temperature is 100°C, and the drying time is 2 h; the hot pressing temperature is 150°C, and the pressure is 60 bar.

[0119] Comparative Example 1

[0120] Comparative Example 1 A membrane electrode D1 not doped with P-type semiconductor powder is prepared, and the preparation method includes the following steps:

[0121] (1) Add part of the solvent to the anode catalyst and thickener and disperse them by ball milling, then add the dispersant, binder and the remaining solvent and stir at a low speed for 10 hours; wherein the anode catalyst is NiCo2O4, the thickener is a modified polyurea thickener, the dispersant is an acrylic copolymer, the binder is a polytetrafluoroethylene resin, and the solvent is water; the mass ratio of the anode catalyst to the thickener, dispersant, binder and solvent is 1:0.005:0.03:0.6:1, and the anode slurry is obtained;

[0122] The cathode catalyst and thickener are added to a part of the solvent and dispersed by ball milling, and then the dispersant, binder and the remaining solvent are added and stirred at a low speed for 12 hours; wherein the cathode catalyst is NiO / Ni, the thickener is a modified polyurea thickener, the dispersant is an acrylic copolymer, the binder is a polytetrafluoroethylene resin, and the solvent is; the mass ratio of the cathode catalyst to the thickener, dispersant, binder and solvent is 1:0.01:0.05:0.4:0.5, and a cathode slurry is obtained;

[0123] (3) The anode slurry is applied to one side of the diaphragm with a spray gun, and the cathode slurry is applied to the other side. The thickness of the slurry applied on the anode side of the diaphragm is 50 μm, and the thickness of the slurry applied on the cathode side is 50 μm. After coating, it is placed in a vacuum oven for drying, and then hot-pressed to prepare a conductive membrane electrode. The drying temperature is 100°C and the drying time is 2 h. The hot-pressing temperature is 150°C and the pressure is 60 bar.

[0124] Comparative Example 2

[0125] Comparative Example 2: A membrane electrode D2 in which an N-type semiconductor powder is doped in the anode catalyst layer is prepared. The method for preparing the membrane electrode in this embodiment is the same as that in Example 1, and the difference from Example 1 is that:

[0126] In step (2), the mass ratio of the anode catalyst to the P-type semiconductor nanopowder is 1:0.02; the thickness of the slurry coated on the anode side of the diaphragm is 50 μm, and the thickness of the slurry coated on the cathode side is 30 μm.

[0127] Performance Testing

[0128] (1) Stack test

[0129] The 400 cm prepared in Examples 1-7 and Comparative Examples 1-2 2 The membrane electrode was placed at 400 cm 2 The single-chamber electrolysis fixture was used for testing, and a constant current electrolysis was performed with an electrolysis current of 160A and a current density of 0.4A / cm 2 The tested voltages are shown in Table 1.

[0130] Table 1

[0131]

[0132] As can be seen from Table 1, by making the semiconductor particles in the catalyst layer contact with the semiconductor layer to form a PN junction, the voltage of the electrolysis chamber is significantly reduced, indicating that the electrolysis efficiency of the membrane electrode is improved, further saving energy consumption.

[0133] (2) Electrochemical active area test

[0134] The membrane electrodes prepared in Examples 1-7 and Comparative Examples 1-2 were subjected to electrochemically active area ECSA test, and the test method was as follows:

[0135] The membrane electrodes prepared in Examples 1-7 and Comparative Examples 1-2 were used as working electrodes and tested using electrochemical impedance spectroscopy (EIS) at a frequency of 0.1-10000 Hz, an amplitude of 5 mV, and a reference voltage of 1.6-1.9 V. The dual capacitance Cdl was calculated, and the electrochemical active area ECSA = Cdl / Cs. The test results are shown in Table 2.

[0136] Table 2

[0137]

[0138] The larger the electrochemical active area of ​​the electrode, the higher the activity. From the data in Table 2, it can be seen that after adding semiconductor nanopowder that can form a PN junction to the membrane electrode, the utilization rate of the catalyst is improved, and the internal catalyst is fully utilized.

[0139] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0140] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0141] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A membrane electrode for producing hydrogen by alkaline water electrolysis, comprising: A diaphragm and an anode catalyst layer and a cathode catalyst layer respectively arranged on both sides of the diaphragm, characterized in that the surface of the anode catalyst layer and / or the cathode catalyst layer is covered with a semiconductor layer on a side different from the diaphragm; the gaps between the catalysts in the anode catalyst layer and / or the cathode catalyst layer are filled with semiconductor particles of a conductivity type opposite to that of the semiconductor layer, the semiconductor particles are in direct contact with the semiconductor layer to form a PN junction, and can be electrically catalytically conductive with the catalyst; The semiconductor particles in the anode catalyst layer are P-type semiconductor powders, and the semiconductor layer in contact with the anode catalyst layer is a first semiconductor layer; the first semiconductor layer includes a film layer composed of an N-type semiconductor or a support substrate loaded with an N-type semiconductor; The semiconductor particles in the cathode catalyst layer are N-type semiconductor powders, and the semiconductor layer in contact with the cathode catalyst layer is a second semiconductor layer; the second semiconductor layer includes a film layer composed of a P-type semiconductor or a support substrate loaded with a P-type semiconductor; The catalyst in the anode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys, oxides or metal salts; the catalyst in the cathode catalyst layer is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts; The N-type semiconductor is selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4, Fe2O3 and BaTiO3; the P-type semiconductor is selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3, Bi2Te3 and MoO2; The mass ratio of the catalyst to the semiconductor particles is 1:(0.05-0.5).

2. The membrane electrode according to claim 1, wherein: The film layer composed of the N-type semiconductor or the film layer composed of the N-type semiconductor has a thickness of 1-30 μm; The support substrate is selected from nickel mesh, titanium mesh, molybdenum mesh, stainless steel mesh, porous nickel, porous titanium, foamed nickel and foamed titanium; The mesh numbers of the nickel mesh, titanium mesh, molybdenum mesh and stainless steel mesh are 40-100 meshes; the porosity of the porous nickel, porous titanium, foamed nickel and foamed titanium is 40-95%.

3. The membrane electrode according to claim 1, wherein: The particle size of the semiconductor particles is 10-50 nm; The particle size of the catalyst is 0.05-10 μm.

4. The membrane electrode according to claim 1, wherein: The thickness of the anode catalyst layer is 10-200 μm; The thickness of the cathode catalyst layer is 1-200 μm.

5. The membrane electrode according to claim 4, wherein: The thickness of the anode catalyst layer is 20-100 μm; The thickness of the cathode catalyst layer is 5-100 μm; The mass ratio of the catalyst to the semiconductor particles is 1:(0.05-0.2).

6. The membrane electrode according to any one of claims 1 to 5, wherein: The diaphragm is selected from one or more of a polyphenylene sulfide (PPS) diaphragm, a polyetheretherketone fiber diaphragm and a polysulfone fiber diaphragm.

7. The membrane electrode according to claim 1, wherein: The catalyst in the anode catalyst layer is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy; The catalyst in the cathode catalyst layer is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2.

8. A method for preparing a membrane electrode according to any one of claims 1 to 7, characterized in that: The method includes: preparing anode slurry and / or cathode slurry doped with semiconductor particles respectively; Applying the anode slurry and cathode slurry to both sides of the diaphragm respectively; Coating a semiconductor compound film layer having a conductivity type opposite to that of the semiconductor particles on the catalyst coating layer containing the semiconductor particles to form a membrane electrode; and / or The slurry containing semiconductor particles is formed into a catalyst layer and a support substrate is covered on the catalyst layer. The support substrate carries a semiconductor compound of opposite conductivity type to the semiconductor particles.

9. The method according to claim 8, wherein: The method for forming a membrane electrode and forming a catalyst layer from a slurry containing semiconductor particles comprises vacuum drying and hot pressing, the drying temperature is 50-150° C., the drying time is 1-3 hours; the hot pressing temperature is 80-200° C., and the hot pressing pressure is 20-100 bar.

10. The method according to claim 8, wherein: The method for preparing the anode slurry and / or cathode slurry doped with semiconductor particles comprises: Taking an anode catalyst and a P-type semiconductor powder and mixing them evenly to obtain an anode mixed powder; Taking cathode catalyst and N-type semiconductor powder and mixing them evenly to obtain cathode mixed powder; The anode mixed powder or cathode mixed powder is uniformly stirred with a thickener, a dispersant, a binder and a solvent to obtain an anode slurry or a cathode slurry; The amount of the semiconductor particles is 5-50wt% based on the weight of the catalyst in the anode slurry or the cathode slurry; The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):

1.

11. The method according to claim 10, wherein: The binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyethersulfone and fluororesin; The dispersant is a phosphate dispersant or an acrylic dispersant; The thickener is selected from one or more of cellulose ether thickeners, polyurethane thickeners and modified polyurea thickeners; The solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol.

12. The method according to claim 11, wherein: The dispersant is selected from one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt; The solvent is selected from one or more of water, ethanol and isopropanol.

13. An electrolytic cell, characterized in that: The electrolytic cell is provided with the membrane electrode according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Molybdenum carbide / carbon nanoparticle hydrogen production catalyst synthesized using ink

    CN111905783B

  • Method for preparing efficient water electrolysis hydrogen evolution catalyst through chemical plating method

    CN113684493A

  • Membrane electrode for water electrolysis and preparation method thereof

    CN101781769A

  • Fuel cell catalyst slurry, electrode and preparation methods of two

    CN110534761A

  • Conductive film electrode and preparation method and application thereof

    CN117926314A